A redefinição da noção de cidadania no supercapitalismo: de cidadão a consumidor - Marques, Felipe Meira (2014)
Faced with an increasing influence of economic power in the daily lives of citizens, the present study aims to clarify how these changes are occurring. For this, observe an increase of individuals, private interests, before deriving a perspective of the community. Part of citizens bother more when a right exclusively yours, especially the consumer is injured, than when a right that struck the collective. This new moment is the result of a slow and gradual transformation, but intensified around the 80s and 90s, reaching its peak now. The consumerism, leveraged with supercapitalism, forged ahead quickly. New identities began to emerge. The citizen now withdraws its conflict with reality, its tension with the world, through consumption. In addition, new identities are reconfigured. New styles are extracted from consumption. Citizenship, prior work-related, can now be linked with which products the person uses. The Model of citizenship based on a social and political declines. This new model is exclusionary, unequal, and carries very serious consequences for the exercise of democracy. Citizenship is increasingly linked to consumption in new identities. The citizen is considered no longer belonging to a state, or a job, but to consumption. It seeks to highlight the political and participatory citizenship before a consumerist citizenship. Putting people like true politicians, able to take charge of their development and not allow economicism disproportionately affects the well being and the political interests of the community.